COVID‐19 and Ischemic Stroke: Clinical and Neuroimaging Findings. Issue 1 (28th September 2020) - Naval‐Baudin, Pablo; Rodriguez Caamaño, Isabel; Rubio‐Maicas, Cecilia; Pons‐Escoda, Albert; Fernández Viñas, Maria Montserrat; Nuñez, Ana; Cardona, Pere; Majos, Carles; Cos, Monica; Calvo, Nahum
ABSTRACT: BACKGROUND AND PURPOSE: SARS‐CoV‐2 causes multiorgan disease due to altered coagulability and microangiopathy. Patients may have an increased risk of cerebrovascular accidents (CVA). Our objective was to analyze clinical and neuroimaging characteristics of patients with ischemic CVA during the pandemic peak in our region, in order to identify atypical presentations. METHODS: We performed a cross‐sectional analysis of patients admitted under code‐stroke protocol to our center with a final diagnosis of ischemic brain infarction. We analyzed the main imaging and demographic characteristics and reviewed neuroimaging for atypical presentations. RESULTS: One‐hundred patients with confirmed ischemic CVA were included. Nineteen had positive polymerase chain reaction testing for SARS‐CoV‐2 on admission. These patients had a lower prevalence of proximal arterial occlusion on imaging, higher in‐hospital mortality, and worse baseline disability. No differences were identified in affected vascular territory, volume of infarction, initial CT stroke score, prevalence of hemorrhagic transformation, gender, age, cardiovascular risk factors, time to admission, symptom severity on entry, or decision to treat with thrombolysis or mechanical thrombectomy. Prevalence of COVID‐19 in our code‐stroke sample was higher than that for our province during this time period. CONCLUSION: The COVID‐19 group had more in‐hospital mortality, less proximal arterial occlusion on CT or MR angiography, and lower baseline modified Rankin Scale score. We suggest a possibly higher proportion of microangiopathic involvement or undetected distal large‐vessel occlusion in the COVID‐19 stroke group. Excess mortality was explained by severe respiratory failure. Otherwise, stroke patients with COVID‐19 did not differ demographically or clinically from those without the illness.